2022
DOI: 10.31501/rbpe.v11i1.12342
|View full text |Cite
|
Sign up to set email alerts
|

Reasons to exercise among college men from Argentina, Brazil, United States of America and France

Abstract: This study aimed to evaluate the relationship between reasons for exercising, the body mass index and concerns about exercise routine, food and appearance among male college student from Argentina, Brazil, France and the USA. Five hundred sixty nine male college students (18-30 years old) answered an online questionnaire composed of sociodemographic questions, nutritional status, physical exercise data and eating attitudes. The effect of the country, type of exercise and reasons for exercising over other varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…For example, Forbes et al [ 39 ] found higher scores for body dissatisfaction and lower scores for eating disorders in Brazilian women compared to U.S. women. A study by Carvalho et al [ 50 ] highlights the importance of exercise in both countries yet shows that U.S. men have a higher weekly average of exercises than Brazilian men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Forbes et al [ 39 ] found higher scores for body dissatisfaction and lower scores for eating disorders in Brazilian women compared to U.S. women. A study by Carvalho et al [ 50 ] highlights the importance of exercise in both countries yet shows that U.S. men have a higher weekly average of exercises than Brazilian men.…”
Section: Discussionmentioning
confidence: 99%
“…These cultural differences are intriguing and suggest that there are differences in the meaning of exercise among these two cultures. In a previous cross-cultural study by de Carvalho et al [ 50 ] Brazilians were more likely to respond that they exercise for “weight loss” whereas Americans more often said “health.” Perhaps when it comes to compulsive exercise, the higher levels of concern for health among Americans is now reflected in concerns more explicitly for weight loss (given the obesity epidemic in the U.S. today). Perhaps Brazilians who exercise more compulsively find that their moods are affected when they do not or cannot exercise and that now is a stronger motivation that weight loss.…”
Section: Discussionmentioning
confidence: 99%